Calcification and ecological depth preferences of the planktonic foraminifer Trilobatus trilobus in the central Atlantic - Stergios D. Zarkogiannis (Royal Society Open Science)
Understanding the controls behind the calcification and distribution of planktonic foraminifera in the modern ocean is important when these organisms are used for palaeoceanographic reconstructions. This study combines previously reported shell mass data with new shell geochemistry, light microscopy and X-ray micro-computed tomography analyses to dissect various parameters of Trilobatus trilobus shells from surface sediments, investigating the factors influencing their biometry. The goal is to understand which aspects of the marine environment are critical for the calcification and vertical distribution of this species. Trilobatus trilobus is found to produce larger, thinner and overall lighter shells in equatorial regions than in subtropical gyre regions, where the shells are up to 4% smaller, more than 60% thicker and approximately 45% heavier. The skeletal mass percentage together with other calcification metrics (shell weight and thickness) are found to depend primarily on ambient seawater salinity rather than carbonate chemistry. In line with their degree of calcification, on the basis of geochemically reconstructed apparent calcification depths, this group of organisms is found shallower in the water column at the Equator and the subtropical gyres, while its habitat deepens in between these regions at the extra-equatorial sites. Furthermore, it is demonstrated that in the (central) Atlantic, it occupies a density layer slightly below the salinity maximum isopycnal at various depths, presumably by adjusting its shell properties.